Reduction of symptom after a combined behavioral intervention for reward sensitivity and rash impulsiveness in internet gaming disorder: A comparative study - Zheng, Yang; He, Jinbo; Fan, Liyan; Qiu, Yuting (Journal of psychiatric research, 2022)
Impulsivity is both a core symptom and a key psychological mechanism in Internet Gaming Disorder (IGD), and therefore interventions for impulsivity in IGD have both theoretical and practical value. However, previous related interventions only tended to focus on a single factor of impulsivity and achieved inconsistent results. In this study, based on the theory of two-factor model of impulsivity (reward sensitivity and rash impulsiveness), four groups of IGD subjects were recruited to investigate whether there were different effects of single rash impulsiveness or reward sensitivity intervention versus a combined intervention. By comparing the different factors of impulsivity of the four groups before and after a 15-day intervention, the results showed that: (1) compared with the control group, subjects in the Go/No-go training group only had a significantly lower level of rash impulsiveness, subjects in the Stimulus-Response Compatibility (SRC) training group only had a significantly lower level of reward sensitivity, and subjects in the combined training group had significantly lower levels of both impulsivity; (2) among the three intervention groups, only the subjects in the combined training group had significantly lower IGD scores in the follow-up measure. This study indicated that the behavioral training of Go/No-go and SRC were effective in improving rash impulsiveness and reward sensitivity in IGD, respectively, but the intervention effect of the combined training was better than that of the single training.